PENGARUH LAYANAN ADMINISTRASI TERHADAP KEPUASAN SISWA MTs. UNGGULAN MUKHTAR SYAFA’AT BLOKAGUNG TEGALSARI BANYUWANGI TAHUN PEMBELAJARAN 2019/2020 - Harun Rosid; Fila Nurul Arifin (Jurnal Manajemen Pendidikan Islam Darussalam (JMPID), 2021)
Abstract The purpose of this study was to determine the quality of administrative services at MTs Unggulan Mukhtar Syafaat Benefits Blokagung Tegalsari Banyuwangi. Second, what is the level of satisfaction of the students at MTs Unggulan Mukhtar Syafaat Benefits Blokagung Tegalsari Banyuwangi. Third, is there an effect of service on the satisfaction of students at MTs Unggulan Mukhtar Syafaat Blokagung Tegalsari Banyuwangi. The method in this study uses quantitative data collection used in this study is a questionnaire, observation, and documentation. While the data validity test uses the Product moment formula, to find data reliability using the Cronbach Alpha formula. Then to test the hypothesis using the T-test and F test, while for the normality test using the Kolmogorov-Smirnov formula. In data analysis using Simple Linear Regression analysis. The results of this study indicate that: (1) the quality of administrative services at MTs Featured Mukhtar Syafaat Blokagung Tegalsari Banyuwangi for the 2019/2020 academic year is quite good, because the results of the T-test are 26.038> 1,290 t table., Which means that Ha is accepted; (2) the level of satisfaction MTs Featured students Mukhtar Syafaat Blokagung Tegalsari Banyuwangi Academic Year 2019/2020 is quite good, because the results of the T count is> 1920 ta table, which means Ha is accepted; (3) is there an effect of service on the satisfaction of students of MTs Featured Mukhtar Syafaat Blokagung Tegalsari Banyuwangi Year The 2019/2020 lesson was 87.4% while the remaining 12.6% was influenced by other variables that were not studied, which means that the effect of administrative services on student satisfaction at MTs Unggulan Mukhtar Syafaat Blokagung Tegalsari Banyuwangi is very good.